Consumer Perceptions of Halal Food as Safer and More Ethical: Evidence from Indonesia and Australia - Imam Kanafi; Susminingsih Susminingsih; Heriyanto; Agus Arwani; Farid Saenong; Ahmad Hanif Muntahal Fahmi (Indonesian Journal of Halal Research, 2026)
This study aims to determine whether factors influencing intention to purchase halal food differ across religious and institutional contexts. This study compares Australia's pluralistic market with Indonesia's halal standards. Specifically, this study assesses the influence of social status, moral attitudes, mood, religious beliefs, trust, and ethical values ​​on purchase intention. Data were collected from 425 halal food consumers (325 Indonesians; 100 Australians) using a purposive sampling method and analyzed using multiple linear regression. The measurement model demonstrated high reliability (Cronbach's alpha = 0.916). The results showed that moral attitudes (β = 0.172; t = 2.657; p = 0.008) and religious beliefs (β = 0.295; t = 2.874; p = 0.004) had a significant and positive effect on purchase intention, with religious beliefs being the strongest predictor. In contrast, social status (β = 0.061; p = 0.238), mood (β = 0.087; p = 0.261), trust (β = 0.050; p = 0.128), and ethical values ​​(β = 0.073; p = 0.307) did not have a significant effect. These findings indicate that moral and religious commitment are the primary factors influencing a person's desire to purchase halal food across institutional environments.